Temperature-Compensated Damage Monitoring by Using Wireless Acceleration-Impedance Sensor Nodes in Steel Girder Connection - Dong-Soo Hong; Khac-Duy Nguyen; In-Cheol Lee; Jeong-Tae Kim (International Journal of Distributed Sensor Networks)
Temperature-compensated damage monitoring in steel girder connections by using wireless acceleration-impedance sensor nodes is experimentally examined. To achieve the objective, the following approaches are implemented. Firstly, wireless acceleration-impedance sensor nodes are described on the design of hardware components to operate. Secondly, temperature-compensated damage monitoring scheme for steel girder connections is designed by using the temperature compensation model and acceleration-impedance-based structural health monitoring methods. Finally, the feasibility of temperature-compensated damage monitoring scheme by using wireless acceleration-impedance sensor nodes is experimentally evaluated from damage monitoring in a lab-scaled steel girder with bolted connection joints.